Women’s empowerment, household dietary diversity, and child anthropometry among vulnerable populations in Odisha, India - Ogutu, Sylvester; Mockshell, Jonathan; Garrett, James; Ritter, Thea; Labarta, Ricardo; Alvarez, Diego; Nedumaran, Swamikannu; Gonzalez, Carolina; Gotor, Elisabetta (2024)
Women’s empowerment has been promoted by researchers and development practitioners as one of the most promising strategies to address widespread hunger and malnutrition. However, the relationship between women’s empowerment and dietary diversity and child nutrition has rarely been studied among vulnerable populations or individuals at greater risk of poor physical and social health status. Moreover, the effects of different domains of women’s empowerment on nutritional outcomes, including dietary diversity and child anthropometry, have rarely been examined, especially with panel data. Using two rounds of panel data from 1900 households and fixed effects regression models, we analyze the effect of women’s empowerment on household dietary diversity score (HDDS) and child anthropometry among the particularly vulnerable tribal groups in Odisha, India. We also estimate the effects of various decision-making domains of women’s empowerment on HDDS and child anthropometry to understand which empowerment domains matter for nutrition. Results show that women’s empowerment is positively associated with HDDS (coef. 0.41 food groups; p < 0.1) and reduces the prevalence of underweight (coef. 39%; p < 0.05) and wasting (coef. 56%; p < 0.1) in children but has no effect on the prevalence of child stunting. Women’s empowerment in agricultural input use; output sales; income; food purchases; and credit, group membership, and employment contribute to improved dietary diversity and child nutrition. We conclude that women’s empowerment contributes to improved dietary diversity and child nutrition and is a promising strategy to improve farm household diets and child nutrition among vulnerable populations. Strengthening women’s empowerment through the promotion of women’s access to land and other agricultural inputs, market participation, access to information, capital, and credit is important.